Conflicts : the poetics and politics of Palestine-Israel - Mor, Liron (Fordham University Press, 2024)
Conflicts engages Hebrew and Arabic literature to critically reassess the concept of conflict, both in Palestine-Israel and in general. Drawing on a diverse archive, ranging from the 1930s to the present and from prose and poetry to film and television, it reveals indigenous literary concepts that better theorize the region's antagonisms and mediations, its colonial technologies and anticolonial practices.
Keywords: Arab-Israeli conflict -- Literature and the conflict.; Hebrew literature, Modern -- 20th century -- History and criticism.; Hebrew literature, Modern -- 21st century -- History and criticism.; Arabic literature -- 20th century -- History and criticism.; Arabic literature -- 21st century -- History and criticism.; Conflit israélo-arabe -- Littérature et conflit.; Littérature hébraïque moderne -- 20e siècle -- Histoire et critique.; Littérature hébraïque moderne -- 21e siècle -- Histoire et critique.; Littérature arabe -- 20e siècle -- Histoire et critique.; Littérature arabe -- 21e siècle -- Histoire et critique.; LITERARY CRITICISM / Comparative Literature.; Arab-Israeli conflict -- Literature and the conflict; Arabic literature; Hebrew literature, Modern; 1900-2099; Arabic Literature.; Colonialism.; Comparative Literature.; Concepts.; Conflict.; Critical Theory.; Hebrew Literature.; Israel.; Mizrahi Jews.; Palestine.; Electronic books.; Criticism, interpretation, etc.